Analysis of Abnormal Return and Volume Activity of Telecommunications Sector Shares in Indonesia Before and After Covid-19 - Sumadi Sumadi; Dewi Tamara; Purba Yudha Tama; William William (Syntax Idea, 2021)
The study intends to investigate if there are significant differences in the abnormal return and volume activity of telecommunication companies 90 exchange days before and 90 exchange days after the announcement of the first Covid-19 infection in Indonesia with the Event Study method. The strategies used in this study are quantitative methods with statistical description analysis using different t-test with paired samples. The samples used in this study are EXCL, ISAT, and TLKM companies included in the telecommunications infrastructure sector and listed on the Indonesia Stock Exchange (IDX). The research test results showed that there was no significant difference in the abnormal return and trading volume activity of telecommunication companies in Indonesia. It proves that telecommunication companies' performance in Indonesia is not affected by the Covid-19 pandemic, because the demand for internet and telecommunication services has become the basic need for people to be able to maintain their productivity at home